Influence of the structural changes on cavitation resistance of Al18SiCuMg alloy produced by rheocasting process - Milena Ćosić; Marina Dojčinović; Slobodanka Boljanović (Zaštita Materijala)
The influence of stirring speeds of 1000 and 1500 r/min on the microstructure of Al18SiCuMg alloy was investigated. The smaller size of Si particles of rheocast sample obtained by higher cooling rate and higher stirring speed was achieved. According to the results of cavitation test, the cavitation rate of the rheocast sample produced by 1500 r/min is lower than that of the rheocast sample obtained by 1000 r/min. The different results show that the mass loss as a function of time can be approximated either by liner or quadratic equations.